Role of solvent molecules as a trigger for the crystal phase transition of syndiotactic polystyrene/solvent complex - Gowd, E. Bhoje; Tashiro, Kohji; Ramesh, C. (Macromolecules, 2008)
The phase transitions occurring in the syndiotactic polystyrene-norbornadiene complex were investigated by simultaneous measurements of wide-angle X-ray diffraction (WAXD) and differential scanning calorimetry (DSC). To understand the effect of norbornadiene molecules on the phase-transition behavior, the delta form samples with different contents of norbornadiene were prepared. By heating these samples, we found that the delta-to-gamma transition occurred well below 100 degrees C in a broad temperature range, and the onset of the transition temperature depended on the content of norbornadiene included in the starting sample. The sample without norbornadiene molecules showed the delta-to-gamma transition to be above 100 degrees C. Upon further heating, the gamma form transformed into a mixture of alpha and beta forms in the presence of norbornadiene molecules, whereas the sample without norbornadiene transformed into only the alpha form. In this way, it has been found that the solvent molecules, which are not completely evaporated from the sample but are transiently trapped in the amorphous region because of the slow diffusion, have a significant role in facilitating the phase transitions as well as the transition temperatures in the crystalline region. On the basis of WAXD and DSC results, a phase-transition model has been reasonably constructed.